PENJADWALAN PROYEK DENGAN PRECEDENCE DIAGRAM METHOD (PDM) DAN RANKED POSITION WEIGHT METHOD (RPWM) - Oka Suputra, I Gusti Ngurah (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011, 2012)
In project construction world, many models of project planning have been intensively used, such as a Precedence Diagram Method (PDM). Scheduling on PDM considers dependency between activity and duration of each activity. To deal with the limited resources, hence allocation and resources levelling need to be implemented using Resource Scheduling Method. Activity scheduling priority is based on activities with the minimum floating time. If some activities have the same floating time, a problem arises in determining the priority of scheduling activity. In the Ranked Position Weight Method (RPWM), allocation and resources levelling are based on positional weight of each activity. Positional weight is determined by adding the sum of duration of an activity with the sum of a total duration of all following activities. The value of positional weight of an activity shows a degree of its importance in relation to other activities. The effects of the construction work condition on the project activity should be considered when preparing precedence logic (relationship of interdependency activities).
Keywords: project scheduling, scheduling priority, resources allocation, activity duration, precedence diagram, positional weight